Issues paper about how to design climate bonds for the steel and selected non-ferrous metals sectors - Ingmar Jürgens; Stefanie Berendsen; Katharina Erdmann; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Basic materials production is responsible for 25% of global greenhouse gas (GHG) emissions. However, both, mitigation efforts and results, are limited. While business-as-usual investments are declining, due to concerns about stranded assets and global over-supply of some materials like steel, the policy framework is insufficient for new low-carbon innovation and investments. To catalyse investments into low-carbon innovation and decarbonize the basic materials sector it is necessary to: - Develop a shared understanding of development perspectives, including new technologies, materials and practices. - Identify conducive conditions for climate-friendly innovations and investments. - Explore options for refinement and use of existing and additional policy and market instruments. - Discuss opportunities and challenges related to implementing such instruments. Against this background, this issues paper discusses key elements that need to be considered for climate bonds or green bonds to play a role in financing decarbonisation in the aluminium and steel sector and to the extent that the relevant information was available, also the copper sector. [...]
Keywords: 330; Klimapolitik; Umweltmanagement; Stahlindustrie; Metallindustrie; Deutschland